Договор франчайзинга: экономико-правовой аспект - Аврамова, О. Е.; Тимченко, В. (НТУ "ХПИ", 2010)
В статье рассматриваются вопросы экономического содержания и правового регулирования договора франчайзинга. Приведены понятия классификации франчайзинга и франшизы. Освещен приоритет франчайзинга над другими формами работы в бизнесе в экономических условиях Украины.

Questions of economic maintenance and legal adjusting of agreement of franchising are considered in the article. Concept and classification of franchise are given. An advantage of legal relationship of franchising over the other construction of business in the economic terms of Ukraine is described.
Agreement of franchising: economic-legal aspect
Keywords: франчайзинг; франшиза; заключение договора; риск; правовая регламентация; бизнес